EXPLORING EFL STUDENTS’ EXPECTATIONS OF THE ENGLISH TEACHING PROCESS IN AN INDONESIAN SENIOR HIGH SCHOOL: A QUALITATIVE STUDY AT SMAN 7 BANDA ACEH - Adilla Rizma; Mulyadi Syahputra; Rizka Marlisa Aini (PENDALAS: Jurnal Penelitian Tindakan Kelas dan Pengabdian Masyarakat, 2026)
This study aims to describe the expectations of grade XI students towards the English learning process at SMA Negeri 7 Banda Aceh and the factors that shape these expectations. The research uses a descriptive qualitative approach. Data were collected from 30 purposively selected students through open-ended questionnaires and semi-structured interviews, then analyzed by reflective thematic analysis. The results of the study show that students' expectations are multidimensional, including linguistic, emotional, social, pedagogical, and institutional dimensions. In the linguistic dimension, students expect an increase in fluency in speech, mastery of vocabulary, pronunciation, and grammar. On the emotional and social dimensions, students need a patient teacher, a classroom atmosphere that is safe from negative judgment, and peer support. Pedagogically, students prefer communicative, interactive, and activity-based learning to lectures. Institutionally, students expect the use of technology and the strengthening of English club activities. Speech anxiety is a major obstacle that affects all dimensions of student expectations. These findings underscore the importance of English language learning that is responsive to students' voices.